Coping with vision loss : understanding the psychological, social, and spiritual effects - Langdell, Cheri Colby (Praeger, 2011)
More than one million people in the United States are fully blind or legally blind, suffering impairments from retinal and macular degeneration to eye loss. And as America with Baby Boomers and beyond ages, the numbers of legally blind will double. In this work where the authors are assisted by a blind executive, readers are taken into the world of the legally and fully blind, to understand the practical challenges that creates for the person experiencing vision loss, and also the family members and friends of that person. And the authors, through interviews with experts across fields, as well.